Classroom Techniques Used By The Teacher ToDevelop Students' English Vocabulary Skill At SmpBatik Surakarta In 2015/2016 Academic Year:A Naturalistic Study - Khotimah, Khusnul; , Prof. Dr. Endang Fauziati, M. Hum; , Siti Fatimah, A M.Hum (2016)
This study is aimed at describe (1) classroom technique used by the teacher in teaching English at SMP Batik Surakarta (2) the purposes each classroom technique (3) the students' role (4) the teachers' role (5) the role instructional material. This type of the research is descriptive qualitative research especially naturalistic study in analiyzing data. The method of collecting data in this study are observation, interview, documentation. The results of this study shows that there are some classroom techniques used by the teacher to develop students' English skill especially vocabulary skill such as: a word search puzzle, translation, reading aloud, memorization, and repetition. The teacher has roles as controller, teacher as organizer, teacher as prompter, teacher as resource, teacher as tutor, teacher as observer and teacher as model. The student has roles as planner, student as group, student as tutor, student as monitor and evaluator. There are some materials used by the English teachers such as English textbook, workbook, and dictionary. The conclusion of this research is that the English teacher at SMP Batik Surakarta used various classroom technique in teaching-learning process can developing the students' English skill especially vocabulary skill. From the various classroom techniques make the students interested and enjoyed in teaching-learning English language. The student becomes more active and creative especially in teaching vocabulary skill. Based on the result, classroom technique used by the teacher is very important to make the students interested and enjoyed in teaching-learning process of English vocabulary skill.